HAMBATAN YANG DIALAMI GURU BK DALAM PELAKSANAAN KEGIATAN KUNJUNGAN RUMAH DI SMP DAN SMA NEGERI KOTA PAYAKUMBUH - Sari, Siska Manda (Konselor, 2013)
Through the ministry of guidance and counseling teachers expected students to develop optimally. The reality in schools, there is guidance and counseling teachers who face obstacles in the implementation of home visits. The research was descriptive form, which aims to describe the barriers faced by guidance and counseling teachers in the planning, implementation and follow up of the results of the home visit. The results showed that there is still a lot of guidance and counseling teachers may encounter in the planning, implementation and follow up of the results of the home visit. Keywords: Barriers Teacher BK; Implementation Activities Home Visits